Vloga vojske pri odzivanju na nesrečo - Malešič, Marjan (Teorija in praksa, 2014)
As a general rule, natural disasters do not attract enough attention in the security debate even though globally there were on average almost 400 disasters annually in the 2002-2011 period. On average, they caused 107,000 deaths, affected more than 268 million people, and caused economic damage close to USD 143 billion annually. The increasing number of disasters and their growing intensity makes civilian disaster management structures ever more helpless in coping with the consequences of disasters, thus making the role of the military in this process extremely prominent in the last few years. Further, various arguments have been developed in order to either approve of the military's increased role in disaster management or to oppose it. The analysis of theoretical discourse on the topic enables us to identify the following arguments: utilitarian, functional-humanitarian and security-strategic argument, the argument of militarisation, and the argument of rejection and isolation, respectively. The analysis is followed by a test of the frequency of those arguments in scientific and professional reports in specific cases of selected huge disasters in the above-mentioned period. In the conclusion, we comment on the content and frequency of various arguments and point out the controversies in the collaboration process between civilian and military structures in the disaster management process.
Keywords: Army; Civil-military relations; Civilno-vojaški odnosi; Crisis management; elementarne nesreče; Krizno upravljanje; Naravne nesreče; Natural disasters; nesreče; Vojska